PROGRAM KEMITRAAN MASYARAKAT PENDAMPINGAN USAHA TELUR ASIN MANISE (MASIR, NIKMAT, SEHAT) SEBAGAI TELUR ASIN RENDAH KOLESTEROL DAN KAYA KALSIUM - Nikmatul Iza; As’ad Syamsul Arifin (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2018)
Malang Regency is one of the districts in East Java which is famous for its food business. One of them is the salted egg business run by Mr. Musta'in which is located in Tamanharjo village, Singosari District, Malang Regency. Even though it has only been pioneered for ± 5 years, the business has survived despite being limited to a family business with its own family members. The problem of the home business lies in how efforts must be made to improve the quality of production and nutritional value of salted eggs. The method used in this service is a survey and discussion of planned activities, improving the quality of salted egg production by procuring tools and conducting training and mentoring in the process of making salted eggs MANISE (Masir, Delicious, Healthy) the taste of onions to the packaging stage, increasing the nutritional value of salted eggs with testing cholesterol levels and calcium levels in salted egg products before and after treatment by adding garlic to the dough, and monitoring and evaluating activities. This service activity starts from February to September 2018. The results achieved through this community service program are the completion of several partner problems starting with taste, attractive packaging, and increasing the nutritional value of cracker products that have low levels of cholecolols and are rich in calcium. There are several activities that support the success of service programs such as training and mentoring in making onion flavored salted eggs, steaming, tapping and packaging processes, and can increase sales turnover in new products.